THE EFFECT OF CAPITAL STRUCTURE ON COMPANY VALUE WITH PROFITABILITY AS AN INTERVENING VARIABLE - Muhammad Alif Ghazi Firaz; Ana Susi Mulyani, S.E., M.M. (PT Larva Wijaya Penerbit, 2022)
The purpose of this research is to examine how capital structure (DER) and profitability (ROA) affect firm value (PBV) in manufacturing companies listed on the Indonesia Stock Exchange in the consumer goods industry sector and the pharmaceutical sub-sector between 2015 and 2020. This research is measured by price to book value (PBV) is used as the dependent variable. Then the independent variables used in this study are capital structure (DER) and profitability (ROA) as intervening variables. The population in this study are manufacturing companies in the consumer goods industry sector, with the pharmaceutical sub-sector listed on the Indonesia Stock Exchange during the study period (2015–2020). The sample was selected using purposive sampling with the criteria of always reporting the company's financial reports and annual reports successively. The methods used in this study are descriptive analysis and path analysis, which is the development of multiple regression using the IBM SPSS program. According to the findings of this study, capital structure has a negative impact on profitability and firm value. While profitability has a positive effect on firm value, Then Profitability is not able to mediate the effect of Capital Structure on Firm Value.